Orbital implants in retinoblastoma patients: 23 years of experience and a review of the literature. (25th November 2015) - Mourits, Daphne L.; Moll, Annette C.; Bosscha, Machteld I.; Tan, H. Stevie; Hartong, Dyonne T.
Abstract: Purpose: To evaluate complications of different types of orbital implants following enucleation for retinoblastoma. Methods: We performed a retrospective chart study of all patients that underwent enucleation as treatment of retinoblastoma between April 1991 and June 2013. Events of implant exposure, extrusion (defined as a complete loss of the implant, or a major exposure that could not be closed) and socket abnormalities were analysed for association with implant type and influence of additional external beam radiation therapy (EBRT) and/or chemotherapy. Results: A total of 224 enucleations in 216 patients (eight bilateral) were identified. Mean age at surgery was 1.9 (median 1.5) years. Of the 219 included enucleated eyes, 20 were not replaced by a primary implant and 18 were replaced by an Allen implant. Scleral wrapped hydroxyapatite (HA) and acrylic implants (polymethylmethacrylate) were inserted in, respectively, 79 and 102 cases. In the total population, 29 treatment or implant‐specific events (13.2%) were registered. Main complications were implant exposure n = 10 (4.6%) and extrusion n = 6 (2.7%). The acrylic/sclera group had less exposures or extrusions (5 of 102, 4.9%) compared to the HA/sclera group (10 of 79, 12.7%), although this difference did not quite reach statistical significance (p = 0.06). Additional treatment (chemotherapy and/or EBRT for the fellow eye) was administered in 78 cases (35.8%). The overall complication rate in the entire study population was significantly higher (16.7% versus 5.7%) in the group exposed to additional therapy (OR 3.3; 95% CI 1.30–8.36 p = 0.008). This negative effect of additional therapy was also significant in the combined acrylic/HA group (OR 2.9; 95% CI 0.97–8.46 p = 0.048). Conclusion: Our results suggest a favourable outcome for acrylic implants compared to the HA implant. Additional treatment with chemotherapy and/or EBRT is associated with an increased risk of complications.